Gumboro Disease: Etiology, Epidemiology, Pathology, Diagnosis And Disease Control - Sutiastuti Wahyuwardani; D.R. Agungpriyono; L. Parede; W. Manalu (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
Infectious bursal disease (IBD) or known as Gumboro, is a disease that attacks chicken older than 3 weeks, caused by famili Birnaviridae virus. Gumboro in Indonesia was firstly reported in 1983 and until now is commonly found. Very virulent IBD virus causes high morbidity and mortality that can even reach 100%. Clinical symptoms are exhibited as sluggish chicken, dropped wings and cloacal pasting. At gross examination, the bursa was found swollen, with yellowish fluid or hemorrhagic 3 days after infection. The bursa will get atrophy from 7 days post-infection. Meanwhile, the non virulent IBD virus causes subclinical symptoms. Chicken that survived, became stunted or dwarfed. On gross and histopathological findings, the bursa Fabricius has mild lesion and will recover at 14 days post-infection. Diagnosis of IBD can be determined based on pathological observation, supported by immunohistochemical examination and laboratory confirmation of disease by agar gel immunodiffusion, polymerase chain reaction techniques, antigen capture enzyme linked immunosorbent assay and isolation. Detection of antibodies can be made by serum neutralization technique or enzyme linked immunosorbent assay. Prevention can be done by routine vaccination in the field when the maternal antibodies have declined. The review describes the etiology, epidemiology, pathogenesis clinical symptoms, pathological discription and control of the disease to improve the knowledge of poultry farmer or people who are interested in poultry health. Key words: Gumboro, etiology, epidemiology, pathology, diagnosis